The Employment Dynamics and Economic Contributions of Community College Graduates in Rupandehi District, Nepal - Rana, Ashok; Gautam, Jagannath; Kuwar, Dhan; Chaudhary, Homan; Kharal, Hemchandra (International Research Journal of Parroha, 2023)
This study investigates the role of human resources graduating from Rupandehi district's community colleges in Nepal's economic development. The research emphasizes the need to reduce income and social security disparities across industries, regions, and labor markets for balanced employment opportunities, especially for higher education institution (HEI) graduates. Data from 162 community college graduates in Rupandehi district, spanning 17 colleges, are meticulously collected while adhering to ethical and safety measures. This research provides valuable insights into the status and role of human resources produced by community colleges, benefiting various stakeholders. In the context of Nepal, the study addresses the shift in labor outmigration trends to developed countries for employment opportunities. It explores how graduates effectively convert their skills and knowledge into sustainable income within diverse economic sectors. Higher education institutions (HEIs) are integral to Nepal's economy, producing a dynamic workforce. The study highlights the importance of ensuring that investments in education lead to productive employment outcomes, with many graduates contributing to self-employment and job creation. Employing a mixed-method approach, combining field surveys and HEI data, this research sheds light on the complex interplay between education and employment in Nepal.